Signos linguísticos e imagéticos da intolerância nos zumbis da série In the flesh - Coutinho, Ricardo Sena (2016)
Television series, especially those which involve the mythical figure of zombies, have reached high rates of acceptance and audience nowadays. The general objective of this research is to analyse the configuration on imagistic and linguistic signs in the representation of zombies in the British TV series In the flesh (2013). It is possible to make a symbolic and socio-historical interpretation of the living-dead from the series which suggests the need for acceptance of others and the importance of respect for differences, demonstrating how zombies can function as a rich source of signification to explain and/or represent the world. The research is justified by the very small number of studies which associates Barthes to televisual productions, by the attempt to take the studies on horror genre away from the academic periphery, by the emergency of discussing interpersonal relations which are set up nowadays and, furthermore, by the opportunity to study and analyse our own culture and understand the human being. Although the research relies on the field of cross-disciplinary studies, once it involves film analysis and Cultural Studies, the basis of the research lies in Semiology, proposed by Roland Barthes. Barthes Semiology reveals to be important in the sense of legitimating the existence of duality which makes up the sign, be it linguistic or imagistic, which is denotative and connotative at the same time, the said and the unsaid. For this purpose, we have made use of a few Barthes’s notions, such as the myth, until entering the kitchen of meaning, where Semiology finds the job of studying the mysterious operation through each any message is impregnated with a second meaning, ideological in general, to which Barthes nominates connoted sense. The methodological procedures we have used include document and film analysis and the semiologic project methodology by the French author and aim at demonstrating how the significance of zombies does not consume only the denoting materiality, but affords to wear numerous and changing senses, including metaphorising intolerance, as concluded by the end of the research.